PENGARUH ELEMEN CORPORATE SOCIAL RESPONSIBILITY TERHADAP RENTABILITAS - Ahmad Hijri Alfian; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
The aim/ the objective of this research is for study the effect of the Corporate Social Responsibilities elemen disclosure to one of the financial soundness ratio. this research uses the CSR disclosure index as a measure based on GRI indicators version 3.1. The sample are 23 companies from consumer good’s listed on the Indonesia Stock Exchange (IDX) in the period 2009 to 2011 until total company for the samples are 46 companies. While the analysis method which is used to examine the effect of CSR disclosure on the profitability ratio is using multiple linier regression analysis, classical assumption test and test hypotheses. The result of this research that indicate a significant effect of CSR toward ROE as an analitycal tool of profitability when tested simultaneously. And if tested partially based on elements of CSR, the only of social and environmental performance that significantly impact ROE. Meanwhile, ROE not impact on the labor, human rights and product performance.